2019
DOI: 10.1136/bcr-2018-227043
|View full text |Cite
|
Sign up to set email alerts
|

Limited auricular relapsing polychondritis in a child treated successfully with infliximab

Abstract: Relapsing polychondritis (RP) is a rare progressive and destructive multisystem disorder characterised by recurrent inflammation of cartilaginous structures. It is a rare disease in paediatrics compared with adults. In children, the diagnosis is either delayed or overlooked due to low incidence. Auricular chondritis has been described in more than half of paediatric cases with RP. However, isolated auricular chondritis has not been reported as the only presentation of pediatric-onset RP. We described a lad who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Meanwhile, partial RPC has been reported by Mathew et al [11] as well as in our previous study [6]. Emerging data suggest that limited RPC are not uncommon in clinical practice [6,[17][18][19][20][21][22][23][24].…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Meanwhile, partial RPC has been reported by Mathew et al [11] as well as in our previous study [6]. Emerging data suggest that limited RPC are not uncommon in clinical practice [6,[17][18][19][20][21][22][23][24].…”
Section: Introductionsupporting
confidence: 66%
“…Patients with laryngo-tracheal involvement or auricular in ammation as the only initial feature of the disease [13], sometimes as the sole feature [8,[17][18][19][20][21][22][23][24], have been de ned as limited form of RPC. In our cohort, 52.3% of the patients presented as limited RPC initially and 40.5% of them remained limited form during follow-up, suggesting that limited RPC is not uncommon among Chinese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, partial RPC has been reported by Mathew et al [11] and our previous study [6] , and limited RPC is not uncommon in clinical settings as demonstrated by our previous study [6] and case reports [17][18][19][20][21][22][23][24]. As a result, these patients do not meet with the current criteria.…”
mentioning
confidence: 61%
“…Patients that underwent recurrent chondritis associated with deformity, in accompany with vestibular dysfunction, ocular inflammation, or inflammatory arthritis were diagnosed as partial RPC as suggested by Mathew et al [11]. Limited RPC can also be diagnosed if patients presented with recurrent inflammatory episodes at isolated cartilaginous sites after exclusion of other possible causes and are responsive to glucocorticoids, based on the observations by other groups and our own [8,13,[17][18][19][20][21][22][23][24] and our own experience. Patients younger than 18 years or without complete electronic case files were excluded.…”
Section: Study Populationmentioning
confidence: 97%